The validation of transrectal palpation of genital organs versus hormonal and post slaughter gross findings in bovine: Khamas D.J. and Radhi K.K - j., Khamas D. (The Iraqi Journal of Veterinary Medicine, 2014)
This study was conducted on sixty seven cows of different breeds and ages (non-descriptive cows). The female genital organs were examined carefully through the rectum before slaughter. Blood samples were also collected prior to slaughter to estimate the levels of progesterone and estrogen level. Gross examination of the same genital organs was approved post slaughter. A comparison has been done to assess the accuracy of rectal palpation for diagnosis of some normal and abnormal conditions. The incidence of findings in rectal palpation were 39 (58.2%) normal non-pregnant, 16 (23.88%) normal pregnant and 12 (17.91%) abnormal conditions. While the findings in gross examination were 32 (47.76%) , 18 (26.86%) and 17 (25.37%), respectively , giving a total error of 20.5% divided in to 10.04% for the normal non-pregnant cows , 3% for the normal pregnant cows and 7.46% for the abnormal conditions. In comparison hormonal levels of estrogen and progesterone were highly suggestive to the gross findings. In conclusion, the validity of rectal examination and diagnosis of various conditions in the genital organs was approximately 80%, which is not suggestive and accurate enough to compare with the hormonal and gross findings.